Associação entre indicadores de condição corporal com consumo de ração e desempenho de porcas - Calegari, Solana (2023)
Monitoring the body condition of sows is extremely important to ensure their welfare, health, and productive and reproductive performance. The objective was to review traditional and advanced methods of assessing the body condition of sows, such as visual assessment, caliper, measurement of backfat thickness via Renco, and ultrasound. Understanding and improving these techniques can enhance nutritional management, animal health, and herd management. Additionally, nutrition plays an important role in sow performance both during gestation for building body reserves and during lactation for adequate milk production. Energy and lysine levels need to be balanced to avoid excessive mobilization of body reserves. Sows weighing 220 kg need to consume 6.017 kg of feed per day to meet the requirements (68.59 g/day of lysine and 20,458 kcal/day of energy). Studies demonstrate that visual assessment is indirect or subjective. When evaluating different methodologies, there was a low correlation between visual assessment and backfat thickness (r=0.44) and a moderate correlation between visual assessment and caliper (r=0.54). The caliper avoids subjectivity and requires less training; furthermore, studies demonstrate a high correlation between the caliper and backfat thickness (r=0.88). Backfat thickness evaluation methods such as ultrasound and Renco are more precise and objective. Dorsal fat is associated with the number of piglets weaned per sow. Sows classified as fat consume less feed during lactation, impacting milk production and piglet performance. Managing the body condition of sows is important to ensure better reproductive indices, production efficiency, longevity, and reduced sow mortality. Research shows that lean sows tend to have reproductive problems with longer intervals between farrowing, more abortions, while fat sows have a higher incidence of stillbirths and health problems. Additionally, a linear relationship was observed between sow weight at mating and subsequent performance. Environmental conditions also influence reproductive performance and feed intake of pigs. Studies indicate that temperatures above the thermoneutral zone (16- 24 ºC) result in reduced feed intake, affecting milk production. In warmer environments, sows tend to mobilize more body reserves.